Analysis of genetic diversity and population structure of a worldwide collection of Corchorus olitorius L. germplasm using microsatellite markers. Issue 4 (4th July 2018) - Yang, Zemao; Lu, Ruike; Dai, Zhigang; Yan, An; Chen, Jiquan; Bai, Zhanbing; Xie, Dongwei; Tang, Qing; Cheng, Chaohua; Xu, Ying; Su, Jianguang
ABSTRACT: Jute ( Corchorus spp.) is the second most important global natural fiber crop after cotton. Analyses of the genetic diversity and population structure of the germplasm are useful for improving Corchorus breeding. Recently, limited studies on genetic diversity and population structure in jute have been carried out. In the present study, the genetic diversity and population structure of 453 accessions in Corchorus olitorius L., including cultivars, landraces, genetic materials and wild germplasm, were analyzed using 39 SSR markers. The results showed that C. olitorius populations have moderate genetic diversity with an average gene diversity ( he ) value of 0.322 and polymorphic information content (PIC) value of 0.270 in all accessions. Regarding the geographic distribution, the average he and PIC values were highest in Kenya (0.332, 0.273), followed by Nepal (0.307, 0.259), and China (0.303, 0.253). Among the different germplasm types, the wild germplasm showed higher genetic diversity with an average he value of 0.362 and PIC value of 0.299. The population structure analysis revealed two populations, Pop1 and Pop2; Pop1 was further divided into three subpopulations, and Pop2 was further divided into two subpopulations. These populations were verified by FST statistics, principal coordinate analysis (PCoA) and neighbour-joining trees. This study contributes to the knowledge about levels and distribution of genetic diversity of C. olitorius worldwide and provides clues about the origin of C. olitorius.